DESKRIPSI KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK PADA PENERAPAN MODEL PROBLEM BASED LEARNING KELAS XII IPA SMAN 4 SOLOK - Chyntia Rosyidah Haz (Departemen Matematika, 2021)
This research aims to describe the mathematical communication skills of students who apply the Problem Based Learning model and describe learning activities while the Problem Based Learning model is applied in class XII IPA SMAN 4 Solok. This type of research is Pre-experiment with One Shot Case Study design. The subjects of this study were students of class XII IPA SMAN 4 Solok in the academic year 2021/2022 with class XII IPA 3 as the subject class. The research instrument is a test of mathematical communication skills in the form of essay questions which are analyzed by finding the average class value of the subject then qualified. Based on data analysis, it was found that the average result of the mathematical communication ability test of students in the subject class was 7.94. After the average is qualified, the mathematical communication skills of students who learn by applying the Problem Based Learning model are in the high category. Keywords– Mathematical Communication Skills, Problem Based Learning, Pre-Experiment